2016
DOI: 10.1371/journal.pone.0166512
|View full text |Cite
|
Sign up to set email alerts
|

Winter Activity of Coastal Plain Populations of Bat Species Affected by White-Nose Syndrome and Wind Energy Facilities

Abstract: Across the entire distribution of a species, populations may have variable responses to environmental perturbations. Many bat species experience mortality in large portions of their range during hibernation and along migratory paths to and from wintering grounds, from White-nose syndrome (WNS) and wind energy development, respectively. In some areas, warm temperatures may allow bats to remain active through winter, thus decreasing their susceptibility to WNS and/or mortality associated with migration to winter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 37 publications
5
25
0
Order By: Relevance
“…However, we detected MYLELUSE in three of the five regions (although they were not detected in many cells throughout each region), including one detection in the Coastal Plain. Although this detection was far outside their known historical range [ 56 ], these findings are consistent with a similar study in North Carolina [ 63 ]. The low detections of MYLELUSE and detections across the state likely led to the relatively low predictive performance (AUC = 0.62) of our model and suggests further research is needed on these species.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, we detected MYLELUSE in three of the five regions (although they were not detected in many cells throughout each region), including one detection in the Coastal Plain. Although this detection was far outside their known historical range [ 56 ], these findings are consistent with a similar study in North Carolina [ 63 ]. The low detections of MYLELUSE and detections across the state likely led to the relatively low predictive performance (AUC = 0.62) of our model and suggests further research is needed on these species.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, we did not find support for a predicted effect of Region on LACI and MYAU occupancy. LACI appear to have more widespread summer distributions within our study area than expected ( Fig 5 ) as has also been found in North Carolina [ 63 ]. MYAU were not detected in many cells within the regions they are thought to occupy, possibly due to their preference for forested wetlands [ 16 , 60 ] that occur in small isolated patches and therefore were not heavily surveyed.…”
Section: Discussionsupporting
confidence: 82%
“…North American bat species face several contemporary conservation challenges throughout their range, including threats to habitat from loss and alteration of forested environments, and direct mortality from development of wind energy infrastructure [ 1 , 2 ]. However, transmission of Pseudogymnoascus destructans (Pd), the pathogen that causes white-nose syndrome (WNS), has emerged as the most serious threat to over a dozen species of North American bats that use caves and mines for hibernacula [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of WNS in the Pacific Northwest opens another front in critical efforts to combat bat declines and shortens the timeline for implementing conservation strategies to protect vulnerable bat species. This effort is complicated by the fact that winter hibernation behavior for most western species is poorly understood [ 14 ], yet this is when WNS has the greatest negative impacts on bat populations [ 2 , 15 , 16 ]. Further, little is known about winter roost sites and activity patterns of many bats in western North America.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, this method has increased in popularity with the creation of automated software packages designed for species identification, with some offering real‐time species classification in the field (Russo and Voigt ). Such surveys are now commonly used to assess the presence of endangered species (e.g., Kaiser and O'Keefe ), effects of disturbance such as logging and wind turbines (e.g., Grider et al ), and as a long‐term population monitoring tool (e.g., Loeb et al ). However, the accuracy of the software is subject to debate.…”
mentioning
confidence: 99%